Development of a New Bone‐Mimetic Surface Treatment Platform: Nanoneedle Hydroxyapatite (nnHA) Coating. Issue 24 (27th October 2020) - Eichholz, Kian F.; Von Euw, Stanislas; Burdis, Ross; Kelly, Daniel J.; Hoey, David A.
Abstract: The hierarchical structure of bone plays pivotal roles in driving cell behavior and tissue regeneration and must be considered when designing materials for orthopedic applications. Herein, it is aimed to recapitulate the native bone environment by using melt electrowriting to fabricate fibrous microarchitectures which are modified with plate‐shaped (pHA) or novel nanoneedle‐shaped (nnHA) crystals. Nuclear magnetic resonance spectroscopy, scanning electron microscopy, transmission electron microscopy, and X‐ray diffraction demonstrate that these coatings replicate the nanostructure and composition of native bone. Human mesenchymal stem/stromal cell (MSC) mineralization is significantly increased fivefold with pHA scaffolds and 14‐fold with nnHA scaffolds. Given the protein stabilizing properties of mineral, these materials are further functionalized with bone morphogenetic protein 2 (BMP2). nnHA treatment facilitates controlled release of BMP2 which further enhance MSC mineral deposition. Finally, the versatility of this nnHA treatment method, which may be used to coat different architectures/materials including fused deposition modeling (FDM) scaffolds and Ti6Al4V titanium, is demonstrated. This study thus outlines a method for fabricating scaffolds with precise fibrous microarchitectures and bone‐mimetic nnHA extrafibrillar coatings which significantly enhance MSC osteogenesis and therapeutic protein delivery, and leverages these results to show how this surface treatment method may be applied to a wider field for multiple orthopedic applications. Abstract : In this work, a new method to coat materials with biomimetic nanoneedle hydroxyapatite is developed and characterized. This simple and versatile protocol can be applied to impart a bone‐mimetic topography on the surface of a range of materials. This novel coating significantly drives osteogenesis and has potential applications in orthopedic medical devices, tissue engineering, and drug delivery.